Macrophages and fibroblasts underpin skin immune responses - Makoto Sugaya (Exploration of Immunology, 2021)
There are various types of skin immune responses including inflammatory skin diseases and skin malignancy. Macrophages and fibroblasts are skin resident cells that had been overlooked in terms of immunological research targets. In this review, cross talk among macrophages, fibroblasts, and migratory immune cells in skin diseases such as atopic dermatitis (AD), contact hypersensitivity, psoriasis, systemic sclerosis, melanoma, and cutaneous T-cell lymphoma is described. Macrophages are important in AD by antigen-presenting phagocytosis, production of inflammatory cytokines, removal of apoptotic cells, and mediating clusters between dendritic cells (DCs) and T cells. They are also increased in lesional skin of psoriasis, especially in stable plaques, and an increased ratio of M1/M2 macrophages and tumor necrosis factor-α production by macrophages are essential for development of psoriasis. The progression of skin malignancy is mediated by macrophages through promotion of tumor survival pathways via expression of cytokines and growth factors, interaction with regulatory T cells (Tregs) and myeloid-derived suppressor cells, and suppression of function of tumor-infiltrating T cells by immunosuppressive cytokines and programmed death-ligand (PD-L)1. Fibroblasts play important roles in development and maintenance of AD lesions through expression of CC chemokine ligand (CCL)17, CCL11, CCL26, C-X-C motif chemokine ligand (CXCL)12, CCL19, and periostin, interacting with T helper (Th)2 cells, natural killer T (NKT) cells, DCs, and keratinocytes. They also play important roles in psoriasis, expressing interleukin (IL)-8 and vascular endothelial growth factor, production of fibronectin, and changes in the proteomic profiles. Fibroblasts have a critical role in the progression skin malignancy via expression of cytokines, suppression natural killer (NK) functions, and establishment of Th2-dominant microenvironment. Thus, cross talk among macrophages, fibroblasts, and migratory immune cells including T cells, DCs, and NK cells in skin diseases is important and those skin-resident cells are attracting therapeutic targets in the near future.